PF-21 Burkholderia cepacia Infection in Python reticulatus - Steven Dwi Purbantoro; Erika Erika; Puveanthan Nagappan Govendan; Yedija Putra Kusuma Wardana Rumbay; Aida Louise Tenden Rompis (Hemera Zoa, 2018)
Boids kept as exotic pets nowadays has increased in recent decades [1]. Its popularity has increased in Indonesia. Without proper husbandry, snakes have higher risk for infection, such as respiratory infection. Respiratory infections are common in captive snakes that could cause severe illness leading to death [2]. Many etiologies say respiratory infection in snakes, are mainly caused by bacteria. Microbiology test is one of the diagnostic method which could be performed to diagnose for a better treatment to identification the cause of the infection. API 20NE kit is a choice. Burkholderia cepacia is a bacterial infection which could occur in pythons. This case reports Burkholderia cepacia finding in a Python reticulatus that had respiratory infection.Burkholderia cepacia Infection in Python reticulatus